The Role Of Accounting Services Offices In Providing Non-Insurance Services To Clients - Graciela Fiamey Baman; Fiona Elma Sabitah; Athaya Zayyan Bakulu; Ernawaty Usman; Abdul Kahar (Universitas Dehasen Bengkulu, 2026)
This study examines the role of non-assurance services provided by Accounting Service Offices (KJA) to clients in response to the increasing demand for professional consulting services beyond traditional audit activities. The objective of this study is to develop a conceptual framework and review previous research on the effects of non-assurance services on audit quality, auditor independence, and client satisfaction. The research employs a systematic literature review method by analyzing relevant academic journals and primary sources. The findings indicate that non-assurance services can enhance service efficiency and provide added value to clients through tax consulting, accounting systems, and other advisory services. However, these services may also create challenges related to auditor independence. Previous empirical studies in Indonesia report mixed results. Some studies suggest that non-audit services positively influence auditor independence and reduce earnings management practices, while others find negative or insignificant effects. These inconsistent findings highlight the need for a comprehensive research model that incorporates corporate governance and professional ethics perspectives. In conclusion, the implementation of non-assurance services in KJA should be supported by strong control mechanisms and adherence to the IAPI Code of Ethics to maintain audit quality, auditor independence, and stakeholder trust.